Effect of Rumen Mega Mineral Bolus Insertion at Calving on Blood Biochemical and Minerals Profile and Postpartum Fertility in Kankrej Cows - Naikoo, Mehrajuddin; Dhami, Arjun J; Parmar, Bhupendra C (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was conducted on 12 pluriparous parturient Kankrej cows of the University Farm, in Anand, randomly divided into two equal  groups (n = 6 each). Group-I cows were administered on the day of calving with a sustained release 80 g mega mineral rumen bolus  (Prepavel® 1 bolus/animal, Neolait, France) intra-ruminal through a specially designed applicator, while group-II animals served as  untreated control. The animals were monitored periodically from the day of calving till 140 days postpartum along with other herd mates.  Blood samples were obtained at 10 days interval in heparinized vacutainers for plasma progesterone, biochemical, and macro-micro  mineral profiling. Among the six Kankrej cows of group-I, only one animal exhibited prominent estrus signs on day 96 postpartum and  conceived at first service (AI) giving CR of 16.66%, while in group-II three cows exhibited estrus between day 73 and 86 postpartum,  and conceived with one or two AI giving CR of 50% by 150 days postpartum. In both the groups, all other cows remained subestrus for  more than 150 days postpartum and conceived very late, though mostly with single service at spontaneous estrus. The mean values of  plasma progesterone (0.74 ± 0.32 to 5.57 ± 0.78 ng/mL), total cholesterol (103.88 ± 3.20 to 237.17 ± 24.66 mg/dL) and triglycerides (17.07  ± 1.16 to 28.29 ± 1.75 mg/dL) differed significantly (p < 0.01) between postpartum intervals in both the groups, but not between groups  at any of the intervals. The values of plasma total protein, calcium, inorganic phosphorus, and magnesium as well as trace elements,  viz., zinc, iron, copper, cobalt, and manganese, however varied insignificantly and inconsistently between intervals and also between  groups from day 0 to day 140 postpartum. Thus, the insertion of Mega mineral ruminal bolus on the day of calving did not influence the  plasma profile of biochemical/ metabolic constituents and macro-micro minerals profile in lactating postpartum Kankrej cows and was  not beneficial in improving postpartum fertility. However, further study on a larger sample size is required to draw a valid conclusion.
Keywords: Blood profile; Intra ruminal placement at calving; Kankrej cow; Mega mineral bolus; Postpartum fertility